2022
DOI: 10.3390/atmos13050669
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spatio-Temporal Variability of Lightning Activity and Wildfires in Western Siberia during 2016–2021

Abstract: This research compares the spatial and temporal variability of lightning activity associated with wildfires in several natural geographical zones of Western Siberia from 2016–2021. The study was based on the World Wide Lightning Location Network (WWLLN) and The Fire Information for Resource Management System (FIRMS) for the warm (April–October) season. It was revealed that areas of hotspots and lightning activity most often coincide in the southwestern part of the territory (near Khanty-Mansiysk and Tyumen), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…If no candidate lightning stroke has a buffer radius of less than 1 km, the search expands incrementally (starting from less than 2 km) until reaching Smax (PerSMinT). The last method is based on the maximum spatiotemporal index "a" (MaxA) [31][32][33][34][35], which does not focus exclusively on the temporal window or buffer radius. Calculation details are as follows:…”
Section: Identifying Igniting Lightning Strokesmentioning
confidence: 99%
“…If no candidate lightning stroke has a buffer radius of less than 1 km, the search expands incrementally (starting from less than 2 km) until reaching Smax (PerSMinT). The last method is based on the maximum spatiotemporal index "a" (MaxA) [31][32][33][34][35], which does not focus exclusively on the temporal window or buffer radius. Calculation details are as follows:…”
Section: Identifying Igniting Lightning Strokesmentioning
confidence: 99%
“…We searched for the most probable fire candidates to be ignited by lightning using an approach based on the formula proposed by [42]. For the first step, we calculated (as in [43]) a proximity index (A) between each observed lightning and the active fire: The choice of such a radius is based on the accuracy of the WWLLN data [20]. We searched for the most probable fire candidates to be ignited by lightning using an approach based on the formula proposed by [42].…”
Section: Methodsmentioning
confidence: 99%
“…We searched for the most probable fire candidates to be ignited by lightning using an approach based on the formula proposed by [42]. For the first step, we calculated (as in [43]) a proximity index (A) between each observed lightning and the active fire:…”
Section: Methodsmentioning
confidence: 99%
“…Lightning is the precursor of about 37% of wildfires in the Tomsk region. Kharyutkina et al [5] have found that the relationship between lightning and hotspots is positive, although the correlation coefficients are low. In addition, they reported that the fire activity caused by lightning in Western Siberia may vary from 5 to 43% during the warm seasons over the investigated period.…”
mentioning
confidence: 99%
“…Lightning-ignited wildfires in the Tomsk region (Western Siberia) have been investigated by Kharyutkina et al [5] in the fifth paper of this Special Issue. They have provided an analysis of the space-time variability of lightning and wildfires in Western Siberia between 2016 and 2021 by searching for lightning candidates of detected fires.…”
mentioning
confidence: 99%